Using collaborative approaches to improve internal displacement data - Levakova, D; Calvo Valderrama, A; Wathum, J; Jusselme, D (Refugee Studies Centre, University of Oxford, 2020)
The magnitude, severity and diversity of internal displacement situations cannot be understood – and much less be adequately responded to – without comprehensive and accurate data. Initiatives such as the GP20 Plan of Action offer examples of good practice for the way forward in this complex area.